Neuropsychological Characteristics of the Confusional State Following Traumatic Brain Injury. (25th January 2019) - Keelan, Rachel E.; Mahoney, Elaine J.; Sherer, Mark; Hart, Tessa; Giacino, Joseph; Bodien, Yelena G.; Nakase-Richardson, Risa; Dams-O'Connor, Kristen; Novack, Thomas A.; Vanderploeg, Rodney D.
Abstract: Objectives: Individuals with moderate–severe traumatic brain injury (TBI) experience a transitory state of impaired consciousness and confusion often called posttraumatic confusional state (PTCS). This study examined the neuropsychological profile of PTCS.Methods: Neuropsychometric profiles of 349 individuals in the TBI Model Systems National Database were examined 4 weeks post-TBI (±2 weeks). The PTCS group was subdivided into Low ( n =46) and High Performing PTCS ( n =45) via median split on an orientation/amnesia measure, and compared to participants who had emerged from PTCS ( n =258). Neuropsychological patterns were examined using multivariate analyses of variance and mixed model analyses of covariance.Results: All groups were globally impaired, but severity differed across groups ( F (40, 506)=3.44; p <.001; ŋp 2 =.206). Rate of forgetting (memory consolidation) was impaired in all groups, but failed to differentiate them ( F (4, 684)=0.46; p =.762). In contrast, executive memory control was significantly more impaired in PTCS groups than the emerged group: Intrusion errors: F (2, 343)=8.78; p <.001; ŋ p 2 =.049; False positive recognition errors: F (2, 343)=3.70; p <.05; ŋp 2 =.021. However, non-memory executive control and other executive memory processes did not differentiate those in versus emerged from PTCS.Conclusions: Executive memory control deficits in the context of globally impaired cognition characterize PTCS. This pattern differentiates individuals in and emerged from PTCS during the acute recovery period following TBI. ( JINS, 2019, 25, 302–313)